RNA-mediated gene silencing can reduce azole resistance, growth and pathogenicity in Pseudocercospora fijiensis - Flor Yuranny Canacuán Melo; Yohana Katerine Suárez Anaya; Vicente Emilio Rey Valenzuela; Juan Gonzalo Morales Osorio; Rafael Eduardo Arango Isaza (PLoS ONE, 2025)
The use of double-stranded RNA (dsRNA) gene silencing has allowed significant advances in the understanding of gene function in many organisms and has the potential for use in disease control. At present, there are no adequate methods to induce gene silencing in Pseudocercospora fijiensis (synonym Mycosphaerella fijiensis), the causal agent of black sigatoka, the most economically important disease affecting banana and plantain production. In this work, we developed methods for effective transient gene silencing in both conidial and mycelial cells of P. fijiensis. The results revealed that treatment with small interfering RNA (siRNA) targeting the PfCyp51 gene was able to reduce the tolerance of a P. fijiensis azole-resistant strain to propiconazole. Furthermore, the selective repression of the Cyp51, adenylate cyclase, and Fus3 genes resulted in inhibited germ tube and mycelial growth, as well as a decrease in the severity of infection in banana leaves. This study suggests that the analyzed genes may be targets for the control of fungicide resistance in P. fijiensis and black Sigatoka disease. RNA interference (RNAi) might be used in the future as a control mechanism in P. fijiensis if appropriate delivery methods are found.